2013
DOI: 10.1302/0301-620x.95b10.31881
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendinopathy

Abstract: The two main categories of tendo Achillis tendon disorder are broadly classified by anatomical location to include non-insertional and insertional conditions. Non-insertional Achilles tendinopathy is often managed conservatively, and many rehabilitation protocols have been adapted and modified, with excellent clinical results. Emerging and popular alternative therapies, including a variety of injections and extracorporeal shockwave therapy, are often combined with rehabilitation protocols. Surgical approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 179 publications
0
22
0
3
Order By: Relevance
“…A wide range of non-invasive and non-operative methods have been developed and modified to treat Insertional Achilles Tendinopathy. However, the success rate is inconclusive due to insufficient clinical evidence [10]. Surgical options are offered for failed non-operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of non-invasive and non-operative methods have been developed and modified to treat Insertional Achilles Tendinopathy. However, the success rate is inconclusive due to insufficient clinical evidence [10]. Surgical options are offered for failed non-operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nontraditional therapies include ultrasound-guided dextrose or polidocanol sclerosing injections, extracorporeal shock wave therapy, and cryoultrasound. 11 In a 50-subject cohort with chronic pain, subjects managed with repetitive loadenergy shockwave therapy demonstrated more favorable results at 4 months than those managed with a 12-week eccentric loading regimen with regard to Victorian Institute of Sports Assessment-Achilles score, pain rating, pain threshold, and tenderness. 12 Significant improvements in pain scores were found after intratendinous injections of 1 mL of 2% lidocaine and 1 mL of 50% dextrose, providing a low-cost and safe treatment with good long-term evidence in 22 cases of CIAT.…”
Section: Nonoperative Managementmentioning
confidence: 95%
“…The rationale for this procedure is based on the fact that numerous studies have shown a direct relation between neovascularisation and pain in chronic Achilles tendinopathy. 1,6,26,27 …”
Section: Minimally Invasive Stripping Of the Paratenonmentioning
confidence: 99%
“…27 The goal of Achilles tendoscopy is to release fibrous adhesions around the tendon and paratenon, to strip pathological neovascularisation of the ventral surface of the tendon and to release the plantaris tendon. 27,28 It has recently been suggested that a thickened, adherent plantaris tendon might be causative, or at least contributory in the development of mid-portion Achilles tendinopathy. [29][30][31] The tendoscopy can be performed through a proximal medial and distal lateral portal, or through two medial portals, using a 2.7 mm scope.…”
Section: Achilles Tendoscopymentioning
confidence: 99%